Abnormal Expression of Glutamate Transporters in Temporal Lobe Areas in Elderly Patients with Schizophrenia - Shan, Dan (2013)
Glutamate transporters facilitate the buffering, clearance and cycling of glutmate and play an important role in maintaining synaptic and extrasynaptic glutamate levels. Alterations in glutamate transporter expression may lead to abnormal glutamate neurotransmission contributing to the pathophysiology of schizophrenia. In addition, alterations in the architecture of the superior temporal gyrus and hippocampus have been implicated in this illness, suggesting that synapses in these regions may be remodeled from a lifetime of severe mental illness and antipsychotic treatment. Thus, we hypothesize that glutamate neurotransmission may be abnormal in the superior temporal gyrus and hippocampus in schizophrenia. To test this hypothesis, we examined protein expression of excitatory amino acid transporter 1-3 and vesicular glutamate transporter 1 and 2 in subjects with schizophrenia (n = 23) and a comparison group (n = 27). We found decreased expression of EAAT1 and EAAT2 protein in the superior temporal gyrus, and decreased EAAT2 protein in the hippocampus in schizophrenia. We didn’t find any changes in expression of the neuronal transporter EAAT3 or the presynaptic vesicular glutamate transporters VGLUT1-2. In addition, we did not detect an effect of antipsychotic medication on expression of EAAT1 and EAAT2 proteins in the temporal association cortex or hippocampus in rats treated with haloperidol for 9 months. Our findings suggest that buffering and reuptake, but not presynaptic release, of glutamate is altered in glutamate synapses in the temporal lobe in schizophrenia.